A systematic review of parental attitude and preferences towards implementation of sexuality education - Yeo Kee-Jiar; Lee Shih-Hui (Institute of Advanced Engineering and Science, 2020)
Parents play a unique role in providing and facilitating their children in acquirement of sexual and reproductive health knowledge. The purpose of this study is to provide an overview of parents’ attitude, preferences towards sexuality education (SE) and factors that contributed to their attitudes and perceptions based on review of relevant literature. The articles were retrieved via electronic databases, and manually examined to identify the studies that addressed the research questions. There were 29 studies with a total of 22,213 parents involved which published in peer-reviewed journals between the year 2000 and 2018 were selected and reviewed systematically. The findings emerged from the review were categorized into three main themes which included parental attitudes, parental preferences towards the implementation of SE and the factors contributed to their attitudes and perceptions. Most studies revealed that parents showed positive attitudes and support the inclusion of SE in school. They preferred age-appropriated SE to be introduced in elementary schools and secondary schools. Some parents supported SE which is aligned with religious teaching and cultural. Demographic factors, parents’ sexuality knowledge, religious and cultural factors could affect parental attitudes and perceptions towards SE. This understanding could be useful for policymakers and educators to encourage collaboration with parents to strengthen the effectiveness of the program and scale up SE to benefit the young generation.